EUROPEANIZATION OF THE BALTIC PARLIAMENTS: EXPECTATIONS AND AGENDA FOR FUTURE RESEARCH - Pukelis, Lukas (Baltic Journal of Political Science, 2012)
The three Baltic states have joined the European Union almost a decade ago, but as of yet no research has been carried out von how the membership in the EU has affected the national political systems of these countries. This article overviews the literature on how EU membership affects the relationship between legislative and executive branches of government and summarizes what expectations could be drawn as to the character and degree of Europeanization of Baltic parliaments, based on the research. It also calls for an empirical study of this matter to measure these expectations against the reality and gives recommendations how it should be carried out.